Rancangan Sistem Informasi Pencatatan dan Pendataan Kesehatan Pegawai di Lingkungan Pemerintah Provinsi Bali - Putu Dian Karmana; Martya Rahmaniati Makful; Artha Prabawa (JSAI (Journal Scientific and Applied Informatics), 2023)
Busyness and high workload as well as low awareness in productive age are factors that cause workers or employees to often neglect their health. Rapid changes in healthcare systems around the world are made possible by advances in information. The purpose of this study is to build an information system for recording and recording the health of ASN and non-ASN employees within the regional government of the province of Bali. The benefit of this research is the formation of a system design as a basis for making information applications regarding health recording/data collection for ASN and non-ASN employees within the Bali provincial government. The Health recording/data collection information system can later be used as an application that can be used by the Bali Provincial Health Office to monitor employee health status and can indirectly be used as a motivator for employees to be able to carry out routine health checks as an effort to prevent and early detect a disease so that can improve the health status of ASN and non-ASN employees within the Bali provincial government.